How Has The Pandemic Situation Changed Our Perception Of Space - Kohoutová, Aneta (My University, 2022)
The vast majority of people in countries affected by COVID-19 felt the radical change the pandemic brought about in almost all aspects of life. Social interactions were cut to a minimum and all cultural activities were banned. In this paper, I evaluate the following question: how did the pandemic situation change our perception of space? I assess what this situation offered us, and how the restrictions imposed due to COVID-19 changed our perception of urban and public space. In order to dig deeper into these questions, I use the ideas of three philosophers who work with a conception of space emphasizing its perception.Through the chosen theories, I introduce public space as something beyond a simple materialistic interpretation. On the one hand, I use Henri Lefebvre’s spatial triad to establish different layers of space. On the other, I argue that the material layer of public space could provide us with valuable experience, according to the phenomenological approach advocated by Maurice Merleau-Ponty and Michel de Certeau. Much of the argument in this paper is based on my own observations during the eight-month lockdown period in the Czech Republic during the spring of 2021.
Jak změnila pandemie naše vnímání prostoru?
Keywords: everyday life; covid-19; perception of space; public space; spatial layers; každodennost; covid-19; veřejný prostor; prostorové vrstvy